1978
DOI: 10.1136/bmj.2.6135.460
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cigarette smoking on gastric emptying.

Abstract: Summary and conclusionsGastric emptying after a test meal was studied in 17 normal volunteers-10 habitual smokers and seven non-smokers. The solid component of the test meal was labelled with technetium and the liquid component with indium. After one meal the habitual smokers smoked two cigarettes. Emptying curves were produced for both technetium and indium, and the differences between curves for meals with and without cigarettes were analysed.Cigarette smoking accelerated the rate at which the liquid compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
1

Year Published

1980
1980
2005
2005

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(27 citation statements)
references
References 11 publications
1
25
0
1
Order By: Relevance
“…The higher susceptibility of the inhibitory system to nicotine may be a reason why previous experiments tended to document a retardant effect on GE of solids, despite considerable differences in the nicotine yield of cigarettes among the experiments. 3,[5][6][7][8][9][10][11] On the other hand, it is probable that, in our subjects, plasma nicotine levels may have risen enough to induce the excitatory response, because nicotine metabolism is slower in Japanese male smokers than in male smokers of other ethnic groups. 30,31 The insignificant trend toward an increase in b after smoking (P = 0.1614) may indicate a potential delay in the early emptying phase due to the initial inhibitory response (Table 1).…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…The higher susceptibility of the inhibitory system to nicotine may be a reason why previous experiments tended to document a retardant effect on GE of solids, despite considerable differences in the nicotine yield of cigarettes among the experiments. 3,[5][6][7][8][9][10][11] On the other hand, it is probable that, in our subjects, plasma nicotine levels may have risen enough to induce the excitatory response, because nicotine metabolism is slower in Japanese male smokers than in male smokers of other ethnic groups. 30,31 The insignificant trend toward an increase in b after smoking (P = 0.1614) may indicate a potential delay in the early emptying phase due to the initial inhibitory response (Table 1).…”
Section: Discussionmentioning
confidence: 78%
“…3,[5][6][7][8][9][10][11] The majority of related research studies have supported a delaying effect of smoking on GE of solids. [5][6][7][8]11 Only one study has found an accelerating effect, 10 but that study did not provide any conclusion on the effect of acute smoking, because it only demonstrated that GE was quicker in chronic smokers than in nonsmokers.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Cigarette smoking is also implicated in delayed gastric emptying of sol ids [44], while liquid emptying is increased [45]. In depressive states, the role of slow gas tric emptying has been suspected in the pro duction of diminished appetite and weight loss.…”
Section: Miscellaneousmentioning
confidence: 99%